1997
DOI: 10.1097/00000421-199702000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy with Concomitant Continuous Cisplatin Infusion for Unresectable Tumors of the Upper Aerodigestive Tract

Abstract: A phase I-II study was initiated in February 1991 of concomitant radiation and cisplatin (CDDP) in the treatment of unresectable head and neck squamous cell carcinomas (n = 12). The first patient was treated palliatively for a cervical recurrence of laryngeal cancer. The 11 other patients had locally advanced (stage IV) previously untreated carcinomas of the oropharynx (n = 9), hypopharynx (n = 1), or cervical node with unknown primary site (n = 1). Standard external radiation was carried out up to a total dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…16,18,[32][33][34][35][36][37][38][39][40] Two trials reported improvements in local control of tumors and survival in pa-*A grade of 0 indicates the absence of an adverse effect, a grade of 1 a minimal effect, a grade of 2 a mild effect, a grade of 3 a moderate effect, and a grade of 4 a severe effect. Eight patients who did not receive radiotherapy were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,[32][33][34][35][36][37][38][39][40] Two trials reported improvements in local control of tumors and survival in pa-*A grade of 0 indicates the absence of an adverse effect, a grade of 1 a minimal effect, a grade of 2 a mild effect, a grade of 3 a moderate effect, and a grade of 4 a severe effect. Eight patients who did not receive radiotherapy were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Renal and haematologic toxicities, and also stomatitis, were the most frequently reported doselimiting factors. In a number of trials, a daily cisplatin dose of 6 mg/m 2 was considered to be the upper limit if the higher-grade toxicities were to be avoided (3,5,37). Even though cisplatin is more toxic than many other anticancer drugs, it has the advantage that its toxicity does not overlap with the radiation-produced side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Daily low-dose cisplatin has been better tolerated in several studies (3,5,37,38). Choi et al (4) have also used the daily low-dose cisplatin schedule, and planned interruptions during the treatment to prevent excessive toxicity.…”
Section: Toxicity Associated With Combined Treatment Schedulesmentioning
confidence: 99%
“…Daily low‐dose cisplatin has been better tolerated in several studies (Bachaud et al. 1997; Jeremic et al.…”
Section: Toxicity Associated With Combined Treatment Schedulesmentioning
confidence: 99%